Complement Is Activated During Normothermic Machine Perfusion of Porcine and Human Discarded Kidneys - Jager, Neeltina M.; Venema, Leonie H.; Arykbaeva, Asel S.; Meter-Arkema, Anita H.; Ottens, Petra J.; van Kooten, Cees; Mollnes, Tom E.; Alwayn, Ian P. J.; Leuvenink, Henri G. D.; Pischke, Soeren E.; , PROPER study consortium (Frontiers in Immunology, 2022)
Background: The gap between demand and supply of kidneys for transplantation necessitates the use of kidneys from extended criteria donors. Transplantation of these kidneys is associated with inferior results, reflected by an increased risk of delayed graft function. Inferior results might be explained by the higher immunogenicity of extended criteria donor kidneys. Normothermic machine perfusion (NMP) could be used as a platform to assess quality and function of donor kidneys. In addition, it could be useful to evaluate and possibly alter the immunological response of donor kidneys. In this study, we first evaluated whether complement was activated during NMP of porcine and human discarded kidneys. Second, we examined the relationship between complement activation and pro-inflammatory cytokines during NMP. Third, we assessed the effect of complement activation on renal function and injury during NMP of porcine kidneys. Lastly, we examined local complement C3d deposition in human renal biopsies after normothermic machine perfusion. Methods: Normothermic machine perfusion with an blood-based perfusion was performed with both porcine and discarded human kidneys for 4 and 6 hours, respectively. Perfusate samples were taken every hour to assess complement activation, pro-inflammatory cytokines and renal function. Biopsies were taken to assess histological injury and complement deposition. Results: Complement activation products C3a. C3d, and soluble C5b-9 (sC5b-9), were found in perfusate samples taken during NMP of both porcine and human kidneys. In addition, complement perfusate levels positively correlated with the cytokine perfusate levels of IL-6, IL-8, and TNF during NMP of porcine kidneys. Porcine kidneys with high sC5b-9 perfusate levels had significantly lower creatinine clearance after 4 hours of NMP. In line with these findings, high complement perfusate levels were seen during NMP of human discarded kidneys. In addition, kidneys retrieved from brain-dead donors had significantly higher complement perfusate levels during NMP than kidneys retrieved from donors after circulatory death. Conclusion: NMP perfusion induces complement activation in porcine and human kidneys, which is associated with release of pro-inflammatory cytokines and in porcine kidneys with lower creatinine clearance. Complement inhibition during NMP might be a promising strategy to reduce renal graft injury and improve graft function prior to transplantation.